1987
DOI: 10.1007/bf01907023
|View full text |Cite
|
Sign up to set email alerts
|

Atrial and ventricular myosins from human hearts II. Isoenzyme distribution after myocardial infarction

Abstract: Human atrial and ventricular myosins were prepared from autopsy specimens from subjects with coronary heart disease. Cardiac myosin light chain isotypes were resolved using two-dimensional gel electrophoresis, whereas myosin isozymes were detected by pyrophosphate gel electrophoresis. Myocardial infarction and associated work overload cause a transition in the light chain complements of the myosins. Thus ventricular myosin light chains were found in pressure overloaded atria and atrial light chains have also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Interestingly, only slow but not fast muscle types revealed a P-LC-polymorphism (19,30) and the P-LC has been implicated in the regulation of shortening velocity of skinned skeletal muscle fibers (21). In the hypertrophied human atrium a shift of the myosin P-LC isoenzyme pattern to the ventricular LC-2 form has been described (3,7,25).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, only slow but not fast muscle types revealed a P-LC-polymorphism (19,30) and the P-LC has been implicated in the regulation of shortening velocity of skinned skeletal muscle fibers (21). In the hypertrophied human atrium a shift of the myosin P-LC isoenzyme pattern to the ventricular LC-2 form has been described (3,7,25).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the extent of NEM enhancement of atrial actomyosin (1.31) was lower than that of ventricular actomyosin (2.00) in young subjects as reported in animals (19,20), while that of atrial actomyosin (1.17) was similarly as low as that of ventricular actomyosin (1.20) in old subjects. Therefore, the transition of myosin isozyme from ventricular-type to atrial-type, as reported in the previous studies (5,6), may be the cause of the decrease of NEM stimulation in ventricular actomyosin Ca2+-ATPase activity with age. However, the Ca2+-ATPase activity of atrial actomyosin in the absence of NEM was higher than the activity of ventricular actomyosin both in young and old subjects.…”
Section: A Tpase Determinationmentioning
confidence: 86%